Anthropogenically driven environmental changes shift the ecological dynamics of hemorrhagic fever with renal syndrome. - Huaiyu Tian; Pengbo Yu; Ottar N Bjørnstad; Bernard Cazelles; Jing Yang; Hua Tan; Shanqian Huang; Yujun Cui; Lu Dong; Chaofeng Ma; Changan Ma; Sen Zhou; et al. (PLoS Pathogens)
Zoonoses are increasingly recognized as an important burden on global public health in the 21st century. High-resolution, long-term field studies are critical for assessing both the baseline and future risk scenarios in a world of rapid changes. We have used a three-decade-long field study on hantavirus, a rodent-borne zoonotic pathogen distributed worldwide, coupled with epidemiological data from an endemic area of China, and show that the shift in the ecological dynamics of Hantaan virus was closely linked to environmental fluctuations at the human-wildlife interface. We reveal that environmental forcing, especially rainfall and resource availability, exert important cascading effects on intra-annual variability in the wildlife reservoir dynamics, leading to epidemics that shift between stable and chaotic regimes. Our models demonstrate that bimodal seasonal epidemics result from a powerful seasonality in transmission, generated from interlocking cycles of agricultural phenology and rodent behavior driven by the rainy seasons.